1985
DOI: 10.1021/jo00212a026
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed and palladium-catalyzed carbonylation reactions with titanium and zirconium alkoxides

Abstract: Benzylic bromides react with titanium or zirconium alkoxides and carbon monoxide, in the presence of catalytic quantities of the dimer of chloro(l,5-hexadiene)rhodium, to give esters in good to excellent yields. Ethers and ketones are byproducts of several of these reactions. Esters are also formed in fine yields from aryl, vinyl, and alkyl bromides by using monometallic [Pd(PPh3)4-Ti(OR)4 as reagent] or bimetallic [Pd(PPh3)4/[l,5-HDRhCl]2-Zr(OR)4 as reagent] catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…In the mid 1980s Alper and co-workers showed that [Pd(PPh 3 ) 4 ] [53] and the bimetallic mixture [Pd(PPh 3 ) 4 ]/ [{RhCl(hd)} 2 ] (hd = 1,5-hexadiene) [54] are active catalysts for the carbonylative synthesis of alkyl esters (Scheme 41). Later, platinum catalysts were used in the carbonylation of alkyl halides under thermal [55] as well as photochemical [56] conditions.…”
Section: Carbonylations Of Alkyl Electrophilesmentioning
confidence: 99%
“…In the mid 1980s Alper and co-workers showed that [Pd(PPh 3 ) 4 ] [53] and the bimetallic mixture [Pd(PPh 3 ) 4 ]/ [{RhCl(hd)} 2 ] (hd = 1,5-hexadiene) [54] are active catalysts for the carbonylative synthesis of alkyl esters (Scheme 41). Later, platinum catalysts were used in the carbonylation of alkyl halides under thermal [55] as well as photochemical [56] conditions.…”
Section: Carbonylations Of Alkyl Electrophilesmentioning
confidence: 99%
“…39 Moreover, this type of bimetallic catalyst system was highly versatile and could employ aluminum, 40 titanium, and zirconium alkoxides as formal alkoxy-transfer agents. 41 In addition to metal alkoxides, formate esters can also be employed as alkoxy-transfer agents. 42 By using zwitterionic rhodium complex, (COD)Rh-(η 6 -C 6 H 5 BPh 3 ) ([Rh]-1) and phase-transfer catalyst, tetra-nhexylammonium hydrogen sulfate ((H 13 C 6 ) 4 N + HSO 4 ), Alper and Amaratunga also developed the first alkoxycarbonylation of benzylic and allylic bromides under phase-transfer conditions.…”
Section: Transition-metal-catalyzedmentioning
confidence: 99%
“…[54][55][56][57] However, catalytic carbonylations of alkyl halides with carbon monoxide (CO) remain very challenging because of the difficult oxidative addition of alkyl halides to the metal center and typically fast and deleteri-ous b-hydride elimination which occur under high temperature or high CO pressure. 40,[57][58][59][60][61][62][63][64] Inspired by our previous work, we devised a new model for palladium-catalyzed oxidative carbonylation using a metal reagent and CO/an alcohol as two nucleophiles to avoid the difficulty of oxidative addition between palladium and alkyl halides. 17 With the advantage of a low first oxidation potential, stability under aqueous conditions, and low toxicity, an alkylindium reagent was employed.…”
Section: Oxidative Carbonylation Of Alkyl-and Arylindium Reagentsmentioning
confidence: 99%